Kapow! - Thirlwell, Adam ([London] : Visual Editions, 2012)
"Kapow! takes place in the thick of the Arab Spring, guided by the highspeed monologue of an unnamed narrator--over-doped, over-caffeinated, over-weight--trying to make sense of this history in real time: with 24 hour broadcasts, YouTube films, lesbian bars in London's East End and far too many newspaper clippings."--Amazon.com.
boek